Morphology of the first instar larva in the tribe Clytrini, with two new descriptions in the subtribe Megalostomina (Coleoptera: Chrysomelidae: Cryptocephalinae) - Agrain, Federico A.; Marvaldi, Adriana E. (Zootaxa, 2009)
Original descriptions and illustrations of the first instar larva of Megalostomis (Heterostomis) lacordairei Lacordaire and of Coscinoptera argentina Burmeister (Clytrini: Megalostomina) are provided. Based on the available information on first instar larvae, the tribe Clytrini is diagnosed. Unique of the larvae of clytrini is the antennal sensorium dome-like. Characters in common between Clytrini, Cryptocephalini, and Chlamisini (Cryptocephalinae) are highlighted, like the body J-shaped (in association with case-bearer habits); frons, clypeus, and labrum fused; spiracles with reticulate peritreme; egg-bursters present on mesoand metathorax, each situated anterior to a very long seta and a short seta ventral to these.